Acrylic hardening coating, preparation method thereof and acrylic product

By using aliphatic polyurethane acrylate containing benzene ring and urea group and acrylic hardened coating with modified titanium dioxide, the problem of insufficient selection of acrylic hardened coating components in the prior art is solved, and the effects of high hardness, strength and light transmission are achieved.

CN119799154AActive Publication Date: 2025-04-11HUIZHOU FABULOUS MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510113252.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

There are few researches on acrylic hardening coatings in the prior art, and insufficient selection of coating components leads to the lack of high-performance acrylic hardening coatings.

Method used

Aliphatic polyurethane acrylate containing benzene ring and urea group is used as the base material, combined with modified titanium dioxide and photoinitiator, acrylic hardening coating is formed under photocuring conditions. By reacting the carbon-carbon double bond of modified titanium dioxide with aliphatic polyurethane acrylate, the hardness and dispersion of the coating are enhanced.

Benefits of technology

The hardness and strength of the acrylic hardening coating are significantly improved, while maintaining high light transmittance, solving the problem of insufficient light transmittance evaluation of acrylic plate hardening coatings in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an acrylic hardening coating, a preparation method thereof and an acrylic product. The acrylic hardening coating is prepared from the following components in parts by mass: 20 to 30 parts of aliphatic polyurethane acrylate, 1 to 3 parts of a photoinitiator, 50 to 70 parts of an organic solvent, 0.1 to 0.3 part of a flatting agent and 1 to 3 parts of modified titanium dioxide. According to the invention, aliphatic polyurethane acrylate containing a benzene ring and a carbamido group is taken as a base material, modified titanium dioxide is taken as a reinforcing agent, an acrylic hardened coating can be formed under photocuring by combining a photoinitiator, and the rigidity of a polyurethane acrylate molecular chain is increased by introducing the benzene ring and the carbamido group, so that the strength of the coating is improved; besides, 5-allyl-3-methoxy methyl salicylate adsorbed by the modified titanium dioxide can react with aliphatic polyurethane acrylate through a carbon-carbon double bond during light curing, so that the hardness of the coating can be remarkably improved while the dispersity of the titanium dioxide in the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic coatings, and in particular to an acrylic hard coating and a preparation method thereof, and an acrylic product. Background Art

[0002] Acrylic, also known as plexiglass, is made of methyl methacrylate monomer (MMA). It has high light transmittance, excellent weather resistance, high surface hardness and surface gloss, good high temperature resistance and good processing plasticity. It is known as the "Queen of Plastics".

[0003] Hardness is one of the parameters that best reflects the production process and technology of cast acrylic sheets, and directly affects whether the sheet will shrink, bend, or deform, and whether cracks will appear on the surface during processing. Applying a hard coating on the surface of an acrylic sheet is an effective method to increase the hardness of the acrylic sheet. For example, CN119144035A discloses a 6H scratch-resistant acrylic sheet and its preparation method and application, wherein a hard coating is prepared on an acrylic sheet, and the hard coating includes, by mass percentage: 20-60% polyurethane acrylic resin, 5-30% active monomer, 0.5-2% metal oxide nanoparticles, <10% photoinitiator, and the rest are additives. This method quickly forms a hard coating under light curing conditions, which improves the wear resistance and toughness of the acrylic sheet. However, the light transmittance of the acrylic sheet containing the hard coating has not been evaluated. CN103540256A discloses a UV-curable high-hardness anti-fingerprint coating for acrylic and its composite material substrates, wherein the coating comprises the following components in parts by weight: 5 to 10 parts of fluorine-modified acrylate oligomers, 10 to 20 parts of silicon-modified acrylate oligomers, 50 to 65 parts of high-functionality acrylate oligomers, 5 to 7 parts of photoinitiators, and 0.05 to 3 parts of additives. This coating can reach a high hardness of 8H when applied on an acrylic substrate, and has the advantages of high light transmittance and anti-fingerprint. However, the components of this coating contain a variety of organic reagents, and the price of fluorocarbon resin is relatively high, which limits its application.

[0004] At present, there are few studies on acrylic hard coatings and few choices for coating ingredients. It is necessary to provide high-performance acrylic hard coatings. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides an acrylic hard coating, which comprises the following components in parts by mass:

[0006] 20-30 parts of aliphatic polyurethane acrylate, 1-3 parts of photoinitiator, 50-70 parts of organic solvent, 0.1-0.3 parts of leveling agent, and 1-3 parts of modified titanium dioxide.

[0007] The present invention obtains a chain extender by preferentially reacting the amino group of diglycolamine with p-phenylene diisocyanate at low temperature, so that the hydroxyl groups of diglycolamine are located at both ends of the structure and the benzene ring of p-phenylene diisocyanate is located in the middle of the structure. L-lysine triisocyanate is polymerized with polyethylene glycol under the action of a catalyst, and then a chain extender is added for further reaction to obtain an intermediate, which is finally reacted with hydroxyethyl acrylate to obtain aliphatic polyurethane acrylate. The molecular chain of aliphatic polyurethane acrylate contains a urea group that reacts with a benzene ring, isocyanate and an amino group, and the introduction of the benzene ring and the urea group increases the rigidity of the polyurethane acrylate molecular chain, thereby improving the strength of the coating.

[0008] Furthermore, the preparation method of the aliphatic polyurethane acrylate comprises, in parts by mass,

[0009] Mix 10 to 20 parts of p-phenylene diisocyanate and 40 to 60 parts of N,N-dimethylformamide, then add 10 to 15 parts of diglycolamine and stir at 0 to 5°C to obtain a chain extender;

[0010] 15 to 20 parts of L-lysine triisocyanate, 0.01 to 0.03 parts of catalyst, 20 to 50 parts of ethyl acetate and 15 to 20 parts of polyethylene glycol are stirred and mixed, then 5 to 10 parts of chain extender are added and stirred for reaction, and finally 4 to 8 parts of hydroxyethyl acrylate are added and stirred for reaction to obtain aliphatic polyurethane acrylate.

[0011] Further, the catalyst includes at least one of dibutyltin dilaurate, dimethyltin glycolate, and stannous octoate;

[0012] The molecular weight of the polyethylene glycol is 400-6000.

[0013] The chemical properties of titanium dioxide are stable, and adding an appropriate amount of titanium dioxide filler can significantly improve the strength and hardness of polymer-based composite materials. However, as an inorganic material, titanium dioxide has poor compatibility with aliphatic polyurethane acrylate. It is necessary to modify titanium dioxide to improve compatibility based on the fact that it is added to a certain proportion to effectively improve the hardness of the coating. The present invention obtains modified titanium dioxide by adsorbing 5-allyl-3-methoxysalicylic acid methyl ester on titanium dioxide. When the coating is cured under light, the carbon-carbon double bonds of the modified titanium dioxide can react with aliphatic polyurethane acrylate, which can significantly improve the hardness of the coating while improving the dispersibility of titanium dioxide in the coating.

[0014] Furthermore, the preparation method of the modified titanium dioxide comprises, by weight,

[0015] After mixing 5 to 10 parts of titanate, 0.5 to 1 part of hexamethylenetetramine and 80 to 120 parts of a first solvent, performing a solvothermal reaction, collecting insoluble matter and calcining to obtain titanium dioxide;

[0016] 5 to 10 parts of titanium dioxide, 1 to 3 parts of 5-allyl-3-methoxysalicylic acid methyl ester and 50 to 60 parts of the second solvent are stirred and mixed to obtain modified titanium dioxide.

[0017] For titanium dioxide, its specific surface area and particle size distribution have a significant impact on its performance. The present invention also adds β-cyanoalanine during the solvent thermal reaction to regulate the structure of titanium dioxide.

[0018] Furthermore, after the titanate, hexamethylenetetramine and the first solvent are mixed, β-cyanoalanine is added in an amount of 0.05 to 0.1 times the mass of the titanate;

[0019] The solvent thermal reaction is maintained at 160-180° C. for 5-8 hours;

[0020] The first solvent includes at least one of water, ethanol and acetone;

[0021] The second solvent includes at least one of ethanol, acetone, chloroform and ether.

[0022] It should be noted that the type of titanate in the present invention does not need to be strictly limited, and illustratively it can be at least one of tetrabutyl titanate and tetraisopropyl titanate.

[0023] Furthermore, the photoinitiator is at least one of methyl phenylacetoate and 1-hydroxycyclohexyl phenyl ketone.

[0024] Furthermore, the solvent includes at least one of propylene glycol methyl ether and ethyl acetate.

[0025] The present invention also provides a method for preparing the above-mentioned acrylic hard coating, comprising:

[0026] Aliphatic polyurethane acrylate and modified titanium dioxide are added to the solvent and stirred to obtain component A.

[0027] The photoinitiator and the leveling agent are stirred and mixed to obtain component B;

[0028] The component A and the component B are mixed evenly to obtain an acrylic hard coating.

[0029] The present invention also provides an acrylic product, comprising an acrylic material and a coating formed by the acrylic hardening coating coated on the surface of the acrylic material.

[0030] The present invention also provides a method for preparing an acrylic product, comprising:

[0031] The acrylic hard coating is coated on the surface of the acrylic material, and then cured under light to form a hard coating on the surface of the acrylic material to obtain an acrylic product.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention uses aliphatic polyurethane acrylate containing benzene rings and urea groups as a base material, modified titanium dioxide as a reinforcing agent, and can form an acrylic hard coating under light curing in combination with a photoinitiator. The introduction of benzene rings and urea groups increases the rigidity of the polyurethane acrylate molecular chain, thereby improving the strength of the coating; in addition, 5-allyl-3-methoxysalicylic acid methyl ester adsorbed by the modified titanium dioxide can react with the aliphatic polyurethane acrylate through carbon-carbon double bonds during light curing, thereby improving the dispersibility of titanium dioxide in the coating and significantly improving the hardness of the coating. DETAILED DESCRIPTION

[0034] Some of the raw materials used in the examples and comparative examples of the present invention are described as follows:

[0035] Polyethylene glycol, molecular weight 600, model PEG600, purchased from Shandong Longhui Chemical Co., Ltd.;

[0036] Leveling agent, model BYK333, was purchased from BYK Chemical Co., Ltd.

[0037] Other raw materials not mentioned are common raw materials. The above content is only to help illustrate the present invention and shall not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them by themselves. These contents will not be repeated in the examples.

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] A method for preparing an acrylic hard coating, comprising the following steps:

[0042] S1, weigh 2.5kg aliphatic polyurethane acrylate, 0.1kg methyl phenylacetonate, 0.1kg 1-hydroxycyclohexyl phenyl ketone, 6kg propylene glycol methyl ether, 1kg ethyl acetate, 0.015kg leveling agent, and 0.2kg modified titanium dioxide;

[0043] S2, mixing aliphatic polyurethane acrylate, modified titanium dioxide, propylene glycol methyl ether and ethyl acetate, and stirring at a speed of 350 rpm for 15 minutes to obtain component A;

[0044] S3, stirring methyl phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone and a leveling agent at a speed of 300 rpm for 10 min to obtain component B;

[0045] S4. Component A and component B are mixed and stirred at a rotation speed of 500 rpm for 10 min to obtain an acrylic hard coating.

[0046] Wherein, the preparation method of aliphatic polyurethane acrylate is:

[0047] T1, 1.5 kg of p-phenylene diisocyanate was mixed with 5 kg of N, N-dimethylformamide, and then 1.25 kg of diglycolamine was added and stirred at 2 ° C and 350 rpm for 2 h, the product was transferred to ethyl acetate to collect the precipitated solid, washed with ethyl acetate three times, and vacuum dried to obtain a chain extender;

[0048] T2. 1.8 kg of L-lysine triisocyanate, 0.002 kg of dibutyltin dilaurate, 3.5 kg of ethyl acetate and 1.6 kg of polyethylene glycol 600 were stirred and mixed at a speed of 350 rpm for 1 hour, and then 0.8 kg of chain extender was added and the stirring reaction was continued for 3 hours. Finally, 0.5 kg of hydroxyethyl acrylate was added, and the stirring reaction was continued for 2 hours. Then, the excess solvent ethyl acetate was rotary evaporated to obtain aliphatic polyurethane acrylate.

[0049] The preparation method of modified titanium dioxide is:

[0050] V1. Mix 0.8 kg of tetrabutyl titanate, 0.08 kg of hexamethylenetetramine, and 10 kg of 75% ethanol aqueous solution, stir at 350 rpm for 15 min, transfer to 175 ° C for solvent thermal reaction for 6 h, cool naturally after completion, collect insoluble matter, wash with water and ethanol three times respectively, place at 120 ° C for drying, and transfer to 500 ° C for calcination in air atmosphere muffle furnace for 2 h to obtain titanium dioxide;

[0051] V2. 0.75 kg of titanium dioxide, 0.2 kg of 5-allyl-3-methoxysalicylic acid methyl ester and 5 kg of chloroform were mixed and stirred at 350 rpm for 2 h. The mixture was filtered and dried at 120° C. to obtain modified titanium dioxide.

[0052] Example 2

[0053] Compared with Example 1, the difference is that the preparation method of modified titanium dioxide is:

[0054] V1. 0.8 kg of tetrabutyl titanate, 0.08 kg of hexamethylenetetramine, 0.04 kg of β-cyanoalanine and 10 kg of 75% ethanol aqueous solution were mixed and stirred at 350 rpm for 15 min, and then transferred to 175 ° C for solvent thermal reaction for 6 h. After the reaction, the insoluble matter was collected by natural cooling and washed with water and ethanol three times respectively, dried at 120 ° C, and then transferred to 500 ° C for calcination in an air atmosphere muffle furnace for 2 h to obtain titanium dioxide;

[0055] V2. 0.75 kg of titanium dioxide, 0.2 kg of methyl 5-allyl-3-methoxysalicylate and 5 kg of chloroform were mixed and stirred at 350 rpm for 2 h. The mixture was filtered and dried at 120° C. to obtain modified titanium dioxide.

[0056] Example 3 and Example 4

[0057] Compared with Example 2, the difference is that the masses of β-cyanoalanine in step V1 of the method for preparing modified titanium dioxide are 0.06 kg and 0.08 kg respectively.

[0058] Comparative Example 1

[0059] Compared with Example 1, the difference is that the preparation method of aliphatic polyurethane acrylate is:

[0060] 1.8 kg of L-lysine triisocyanate, 0.002 kg of dibutyltin dilaurate, 3.5 kg of ethyl acetate, and 2.4 kg of polyethylene glycol 600 were stirred and mixed at a speed of 350 rpm for 4 hours, and finally 0.5 kg of hydroxyethyl acrylate was added. After stirring and reacting for 2 hours, the excess solvent ethyl acetate was rotary evaporated to obtain aliphatic polyurethane acrylate.

[0061] Comparative Example 2

[0062] Compared with Example 3, the difference is that the preparation method of aliphatic polyurethane acrylate is:

[0063] 1.8 kg of L-lysine triisocyanate, 0.002 kg of dibutyltin dilaurate, 3.5 kg of ethyl acetate, and 2.4 kg of polyethylene glycol 600 were stirred and mixed at a speed of 350 rpm for 4 hours, and finally 0.5 kg of hydroxyethyl acrylate was added. After stirring and reacting for 2 hours, the excess solvent ethyl acetate was rotary evaporated to obtain aliphatic polyurethane acrylate.

[0064] Comparative Example 3

[0065] Compared with Example 3, the difference is that titanium dioxide is used to replace modified titanium dioxide. The preparation method of titanium dioxide is as follows:

[0066] 0.8 kg of tetrabutyl titanate, 0.08 kg of hexamethylenetetramine and 10 kg of 75% ethanol aqueous solution were mixed and stirred at 350 rpm for 15 min, then transferred to 175°C for solvent thermal reaction for 6 h. After the reaction was completed, the insoluble matter was collected and washed three times with water and ethanol respectively, dried at 120°C, and then transferred to 500°C for calcination in an air atmosphere muffle furnace for 2 h to obtain titanium dioxide.

[0067] Comparative Example 4

[0068] Compared with Example 3, the difference is that titanium dioxide is used to replace modified titanium dioxide. The preparation method of titanium dioxide is as follows:

[0069] 0.8 kg of tetrabutyl titanate, 0.08 kg of hexamethylenetetramine, 0.04 kg of β-cyanoalanine and 10 kg of 75% ethanol aqueous solution were mixed and stirred at 350 rpm for 15 min, then transferred to 175°C for solvothermal reaction for 6 h. After the reaction was completed, the insoluble matter was collected and washed three times with water and ethanol respectively, dried at 120°C, and then transferred to 500°C for calcination in an air atmosphere muffle furnace for 2 h to obtain titanium dioxide.

[0070] Application Examples 1 to 8

[0071] The preparation method of acrylic products, the steps are as follows:

[0072] The acrylic hard coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively evenly coated on the acrylic plate surface by a coating roller. The line speed of the acrylic plate was 3 m / min, and the line speed of the coating roller was 6 m / min. After the coating was completed, the acrylic plate was placed in an oven at 85°C for leveling. 350 mJ / cm 2 A hard coating with a thickness of 50 μm was prepared on the surface of the acrylic plate by irradiation with a mercury lamp.

[0073] Test Case

[0074] The specific surface area and average particle size of the titanium dioxide prepared in the embodiment and the comparative example were tested using a nitrogen adsorption desorption instrument and a laser particle size analyzer. The results are shown in Table 1.

[0075] Table 1 Specific surface area and average particle size of titanium dioxide

[0076] <![CDATA[Specific surface area (m 2 / g)]]> Average particle size (nm) Example 1 35.6 128 Example 2 48.2 89 Example 3 55.7 83 Example 4 46.1 92

[0077] It can be seen that compared with Example 1, the specific surface area of ​​titanium dioxide prepared in Examples 2 to 4 is increased and the average particle size is reduced. This is because the introduction of β-cyanoalanine effectively regulates the structure of titanium species in the initial stage of the solvothermal reaction, making it have richer pores and smaller particle size, larger specific surface area and lower particle size. Such titanium dioxide has more binding sites and can better react with aliphatic polyurethane acrylate.

[0078] Referring to the standards GB / T 6739-2022 "Determination of film hardness of paints and varnishes by pencil method", GB / T 9286-2021 "Scratch test for paints and varnishes" and GB / T 20624.1-2006 "Rapid deformation (impact resistance) test for paints and varnishes Part 1: Drop weight test (large area punch)", the hardness, adhesion and impact resistance of the hard coating of the acrylic products in the application example were tested respectively. The results are shown in Table 2.

[0079] Table 2 Test results of hardness, adhesion and impact resistance of hard coating

[0080]

[0081]

[0082] From the test results in Table 2, it can be seen that the hardness, adhesion and impact resistance of Application Examples 1 to 4 of the present invention are significantly better than those of Application Examples 5 to 8. Comparing Application Example 1 with Application Example 5 and Application Example 2 with Application Example 6, the introduction of benzene rings and urea groups increases the rigidity of the polyurethane acrylate molecular chain, thereby improving the strength of the coating; Comparing Application Example 3 with Application Example 7 and Application Example 8, it is shown that directly adding titanium dioxide cannot significantly improve the hardness of the coating, which is due to the poor dispersibility of titanium dioxide. The 5-allyl-3-methoxysalicylic acid methyl ester adsorbed on the modified titanium dioxide can react with the aliphatic polyurethane acrylate through the carbon-carbon double bond during photocuring, which can significantly improve the hardness of the coating while improving the dispersibility of titanium dioxide in the coating. Thanks to the large specific surface area and small particle size of titanium dioxide, titanium dioxide modified with 5-allyl-3-methoxysalicylic acid methyl ester can be well dispersed in the aliphatic polyurethane acrylate structure under photocuring. The presence of benzene rings and urea groups increases the rigidity of the polyurethane acrylate molecular chain. Application Example 3 has the highest hardness, adhesion, and impact resistance.

[0083] The light transmittance of the acrylic product of the application example was measured with reference to the standard GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”. The results are shown in Table 3.

[0084] Table 3 Light transmittance results of acrylic products in application examples

[0085] Light transmittance (%) Application Example 1 92.2 Application Example 2 92.8 Application Example 3 93.3 Application Example 4 92.6 Application Example 5 91.2 Application Example 6 91.5 Application Example 7 90.3 Application Example 8 90.5 Acrylic sheet 93.5

[0086] It can be seen from the results in Table 3 that the light transmittance of the acrylic product with hard coating constructed in the embodiment of the present invention is very close to that of the acrylic plate substrate.

[0087] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An acrylic hard coating, characterized in that: The following components are included by mass: 20-30 parts of aliphatic polyurethane acrylate, 1-3 parts of photoinitiator, 50-70 parts of organic solvent, 0.1-0.3 parts of leveling agent, and 1-3 parts of modified titanium dioxide.

2. The acrylic hard coating according to claim 1, characterized in that: The preparation method of the aliphatic polyurethane acrylate comprises, by parts by mass, Mix 10 to 20 parts of p-phenylene diisocyanate and 40 to 60 parts of N,N-dimethylformamide, then add 10 to 15 parts of diglycolamine and stir at 0 to 5°C to obtain a chain extender; 15 to 20 parts of L-lysine triisocyanate, 0.01 to 0.03 parts of catalyst, 20 to 50 parts of ethyl acetate and 15 to 20 parts of polyethylene glycol are stirred and mixed, then 5 to 10 parts of chain extender are added and stirred for reaction, and finally 4 to 8 parts of hydroxyethyl acrylate are added and stirred for reaction to obtain aliphatic polyurethane acrylate.

3. The acrylic hard coating according to claim 2, characterized in that: The catalyst includes at least one of dibutyltin dilaurate, dimethyltin glycolate, and stannous octoate; The molecular weight of the polyethylene glycol is 400-6000.

4. The acrylic hard coating according to claim 1, characterized in that: The preparation method of the modified titanium dioxide comprises, by parts by mass, After mixing 5 to 10 parts of titanate, 0.5 to 1 part of hexamethylenetetramine and 80 to 120 parts of a first solvent, performing a solvothermal reaction, collecting insoluble matter and calcining to obtain titanium dioxide; 5 to 10 parts of titanium dioxide, 1 to 3 parts of 5-allyl-3-methoxysalicylic acid methyl ester and 50 to 60 parts of the second solvent are stirred and mixed to obtain modified titanium dioxide.

5. The acrylic hard coating according to claim 4, characterized in that: After the titanate, hexamethylenetetramine and the first solvent are mixed, β-cyanoalanine is added in an amount of 0.05 to 0.1 times the mass of the titanate; The solvent thermal reaction is maintained at 160-180° C. for 5-8 hours; The first solvent includes at least one of water, ethanol and acetone; The second solvent includes at least one of ethanol, acetone, chloroform and ether.

6. The acrylic hard coating according to claim 1, characterized in that: The photoinitiator is at least one of methyl phenylacetoate and 1-hydroxycyclohexyl phenyl ketone.

7. The acrylic hard coating according to claim 1, characterized in that: The solvent includes at least one of propylene glycol methyl ether and ethyl acetate.

8. A method for preparing an acrylic hard coating as claimed in any one of claims 1 to 7, characterized in that: include, Aliphatic polyurethane acrylate and modified titanium dioxide are added to the solvent and stirred to obtain component A. The photoinitiator and the leveling agent are stirred and mixed to obtain component B; The component A and the component B are mixed evenly to obtain an acrylic hard coating.

9. An acrylic product, characterized in that: The invention relates to an acrylic material and a coating formed by the acrylic hardening coating according to any one of claims 1 to 7 coated on the surface of the acrylic material.

10. A method for preparing an acrylic product, characterized in that: include, The acrylic hard coating according to any one of claims 1 to 7 is coated on the surface of an acrylic material, and then cured under light to form a hard coating on the surface of the acrylic material to obtain an acrylic product.

Citation Information

Patent Citations

  • Ultraviolet-curing high-hardness fingerprint-resistant coating for PMMA (Polymethyl Methacrylate) and composite base material of PMMA

    CN103540256A

  • 6H scratch-resistant acrylic plate as well as preparation method and application thereof

    CN119144035A

  • Preparation method of halogen-free intrinsic flame-retardant waterborne polyurethane film

    CN110483735A

  • Transparent thermoplastic polyurethane elastomer

    CN113861372A

  • Bi-component photocurable acrylate composite adhesive and preparation method thereof

    CN118772830A

Cited By

  • Nano heat-insulating hardened coating and preparation method thereof

    CN121108790A